Honesty on Trial: An Experimental Approach - Galarza Arellano, Francisco B. (2024)
We study honesty using a two-player deception game, where players are required to report the group they belong to. The payoffs depend on the decisions of each pair of players, with lying yielding the highest individual payoff. Exploiting a between subjects design, we examine the effect of time (delay and pressure) and information (about the decisions of her peers) on lying and investigate whether these effects differ by gender. Using a sample from two private universities in Peru, we find that, on average, participants lie less in the delay treatment compared to the time pressure treatment, and that only the time pressure treatment shows a differential effect by gender. Additionally, we observe heterogeneity between the two colleges in both cases. Among the numerous potential correlates we analyze, the propensity to follow rules, risk aversion, loss aversion, guilt, and beliefs about others’ honesty all influence individual honesty.